2012
DOI: 10.1016/s0019-4832(12)60056-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin—a novel risk factor in acute myocardial infarction

Abstract: Objectives: To study the relationship of serum ferritin with acute myocardial infarction (AMI) in univariate and multivariate analysis and to assess the relationship of high serum ferritin with established conventional risk factors.Methods: Hospital based case-control study of 75 cases of AMI, and 75 age and equal number of age, and gender-matched controls without having AMI in the age group of 30-70 years.Results: Median serum ferritin levels were significantly higher in cases (220 μg/L) than controls (155… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 22 publications
7
28
0
Order By: Relevance
“…34 Under conditions of high oxidant stress there is increased peroxidation of lipoprotein phospholipids, thereby increasing the LDLuptake by macrophages with increased foam cell formation and atherosclerosis, initiating a potent inflammatory response in the process observed in the form of increased serum ferritin levels. 35 Our finding correlates with prior studies, where it was observed that patients with chest pain and positive cardiac enzyme test were found to have significantly elevated levels of serum ferritin when compared to healthy controls. This study indicates that serum ferritin indirectly enhances the role of LDL-cholesterol in the induction of cardiovascular diseases.…”
Section: Resultssupporting
confidence: 91%
“…34 Under conditions of high oxidant stress there is increased peroxidation of lipoprotein phospholipids, thereby increasing the LDLuptake by macrophages with increased foam cell formation and atherosclerosis, initiating a potent inflammatory response in the process observed in the form of increased serum ferritin levels. 35 Our finding correlates with prior studies, where it was observed that patients with chest pain and positive cardiac enzyme test were found to have significantly elevated levels of serum ferritin when compared to healthy controls. This study indicates that serum ferritin indirectly enhances the role of LDL-cholesterol in the induction of cardiovascular diseases.…”
Section: Resultssupporting
confidence: 91%
“…Recently evidence of association of elevated serum ferritin and increased risk of AMI came from the studies in Asian ethnic population. [5,6,7] These findings strongly support the "iron hypothesis" which suggests that iron, as a catalytic agent, could promote formation of highly reactive oxygen. The reactive oxygen species (ROS) has been implicated in lipid peroxidation and atherosclerosis subsequently leading to AMI.…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, excess iron could be harmful because it is able to catalyse the formation of highly reactive oxygen and hydrogen radicals when present in the unbound state. Transition metal ions, established catalysts of protein, lipid and DNA oxidation, are present at elevated levels in human atherosclerotic plaques, and in some animal models, consistent with the hypothesis that metal ions contribute to both plaque formation and its destabilization (19,21,23), though the role of metal ions remains controversial (16,29).Epidemiological studies have reported an increased incidence of cardiovascular disease (CVD) in subjects with overt iron overload (7,8,19). Recent studies on cardiovascular evaluation and outcome in high-versus low-frequency blood donors have demonstrated improvements in surrogate markers of vascular health such as decreased oxidative stress, and…”
mentioning
confidence: 56%
“…The results of several human studies strongly suggested a relationship between body iron levels and atherosclerosis. According to the epidemiological studies, high systemic iron levels, monitored by serum ferritin levels or transferrin saturation, positively correlated with an increased risk of myocardial infarction (7,18). A protective effect of iron depletion that may have multiple beneficial consequences is decreased availability of redox-active iron in vivo (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation